Poligami dalam Lintas Budaya dan Agama: Meta - Interpretation Approach - Sa'adah, Nurus; Fitria, Vita; Widiastuti, Kurnia (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2015)
Polygamy both discourse and practice has always been a conversation kontroversif and contradictory. Some people regard it as a symbol of patriarchal and marginalization of women. While on the other hand polygamy is considered as part of the expression of faith, in fact is one of the rights that can not be intervened by anyone. Discourse on polygamy still rolling today. This study is not focused on the concept of thought, religious interpretation, certain scientific perspective, as well as studies in general about polygamy. But more to the mapping research on polygamy during the past three decades and the consistency of the results of research conducted along with qualitative explanation. With meta-interpretative approach, researchers are trying to map the writing or research on polygamy as well as finding and distinguishing development, both in terms of religion and culture.